Major agriculture activities in the month of June - Sepat, Seema; Kumar, Dinesh (Indian Farming, 2019)
June is the beginning of major agricultural activities. Monsoon becomes active in the country at the end of the month. Accordingly, farmers can plan the sowing of cereals, pulses, oilseed, vegetables and fodder crops in this month. Proper care of the already planted rice seedlings needs to be continued. If not then sowing of rice should be finished in the first fortnight of June in the nursery area to obtain higher rice seed yield. At the end of this month, some farmers started on rice transplantation. Proper care of crops grown is also an important agricultural work in this month. Therefore, important agricultural activities that need to carry out in this month have been discussed in the paper.